Pengaruh Pendapatan Asli Desa Dan Alokasi Dana Desa Terhadap Belanja Desa Di Kab. Majalengka - Tito Marta Sugema Dasuki (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
All village in Indonesia especially in Majalengka Regency still depent on the transfer fund provided by the government, because the village original income earned by each village is still small. The showing that the village financial independence still low. This research aimed to determine the effect of village original income and village budgetary allocation to the village expenditure. Independen variable in this research is village original income and village budgetary allocation. Dependen variable in this research is village expenditure. Analisis data method using multiple linear regression. The population used in 318 village report data in siskedes. By using Cluster sampling, in this research used 100 samples. Data that used in this research is secondary data, the analysis method used in this research is normality test, multicolinearity test, auto correlation test and heteroscedasticity test. The result of this research showed that village original income has significant influence to the village expenditure and village budgetary allocation significant influence to the village expenditure. Simultaneously village original income and village budgetary allocation have significant influence to the expenditure village.